Decentralizing for a deeper democracy and a more supple state - Jean-Paul Faguet; Ashley Fox; Caroline Pöschl (London School of Economics and Political Science (LSE), Department of International Development, 2015)
Well-designed decentralization can deepen democracy and strengthen the state in five key ways. Decentralizing below the level of social cleavages should undermine secessionism by peeling away moderates from radical leaders. The "fragmentation of authority" critique is mistaken; decentralization transforms the state from a simpler, brittler command structure to one of multilevel complementarity more robust to local failure. Decentralizing services with low economies of scale, with devolved taxation and bail-outs prohibited, should increase accountability. Lastly, the small scale of local politics allows citizens to become political actors, promoting social learning-by-doing, strengthening political legitimacy and 'democratic suppleness' from the grass-roots upwards.
Keywords: 330; Decentralization; state strength; fragile states; social learning; government accountability; political legitimacy; elite capture; secession; subnational governance; public services